Characterization of Calcium Compounds in Opuntia ficus indica as a Source of Calcium for Human Diet - Isela Rojas-Molina; Elsa Gutiérrez-Cortez; Moustapha Bah; Alejandra Rojas-Molina; César Ibarra-Alvarado; Eric Rivera-Muñoz; Alicia del Real; Ma. de los Angeles Aguilera-Barreiro (Journal of Chemistry)
Analyses of calcium compounds in cladodes, soluble dietary fiber (SDF), and insoluble dietary fiber (IDF) of Opuntia ficus indica are reported. The characterization of calcium compounds was performed by using Scanning Electron Microscopy, Energy Dispersive Spectrometry, X-ray diffraction, and infrared spectroscopy. Atomic Absorption Spectroscopy and titrimetric methods were used for quantification of total calcium and calcium compounds. Whewellite (CaC2O4·H2O), weddellite (CaC2O4·(H2O)2.375), and calcite (CaCO3) were identified in all samples. Significant differences (P≤0.05) in the total calcium contents were detected between samples. CaC2O4·H2O content in cladodes and IDF was significantly higher (P≤0.05) in comparison to that observed in SDF, whereas minimum concentration of CaCO3 was detected in IDF with regard to CaCO3 contents observed in cladodes and SDF. Additionally, molar ratio oxalate : Ca2+ in all samples changed in a range from 0.03 to 0.23. These results support that calcium bioavailability in O. ficus indica modifies according to calcium compounds distribution.